Delineating market boundaries in the pharmaceutical industry - Guzman, Ricardo Rafael S.; Abrenica, Maria Joy V. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
Assessments of market power require a definition of the boundaries of the relevant market _ the set of products and associated locations that are substitutable to firms and consumers. In antitrust, the prevailing paradigm by which relevant markets are defined is the Hypothetical Monopolist Test (HMT), a test that identifies the smallest set of products that a hypothetical firm would find profitable to monopolize. While the test is firmly grounded in economic theory, traditional methods to implement it examine consumer responses to price changes in a vacuum, ignoring consumer heterogeneity and institutional features that affect the nature of substitution between products. Failing to accurately define markets can result in misleading assessments of the degree of competition in an industry, leading to costly errors that diminish the efficacy of antitrust enforcement. This paper demonstrates the value of a structural HMT by comparing the size and composition of relevant markets under a SSNIP to a classification based solely on product characteristics. We implement this test in the market for pharmaceuticals where goods are highly differentiated, and several agents are involved in consumer demand. We find that the structural SSNIP test produces relevant markets that are distinct from those defined on the basis of therapeutic characteristics. Markets can be comprised of products from different therapeutic classes and smaller markets can exist within the narrowest possible therapeutic classes. Because relevant markets do not necessarily cleave along clear lines, enforcement agencies and antitrust practitioners should be cautious when delineating markets on the basis of therapeutic properties.
Thesis (M.A. Economics) -- University of the Philippines Diliman
Keywords: Antitrust law -- Economic aspects; Pharmaceutical industry